Anti-proliferative activity of Artemisia marschalliana on cancerous cell lines - Haleh Forouhandeh; Vahideh Tarhriz; Masoumeh Zadehkamand; Parina Asgharian (BMC, 2023)
Abstract Background The genus Artemisia of the Asteraceae family has different species that are used in the treatment of a wide range of diseases, including cancers due to the presence of valuable compounds and important medicinal properties. Various studies on the anti-tumor effect of different species of Artemisia have proven the cytotoxic properties of these plants in cancer treatment, and several anti-cancer compounds of this genus have been purified. Objective The objective of this study was to investigate the cytotoxicity and related mortality mechanisms of Artemisia marschalliana essential oil and extracts. Methods The essential oil and various extracts of Artemisia marschalliana were elicited using a Soxhlet extractor. Anti-cancer to anti-proliferative activity as MTT assay is measuring cancerous and non-cancerous cell viability. In the next step, the strongest extract fractions were obtained by using the vacuum liquid chromatography method. Flow cytometry was applied to identify the mechanism of cell death, and a Real-time polymerase chain reaction test of apoptosis genes, which encode apoptosis-regulating proteins, was measured to confirm the flow cytometry results. Results The strongest extract belonged to dichloromethane extract 60% fraction of the extract on breast cancer cells and 80% fraction on liposarcoma cancer cells showed the most cytotoxicity within 48 h, while, the fractions did not notable cytotoxicity of non-cancerous cells cell. Flow cytometry analysis illustrated the mentioned extract and its fractions kill cancer cell lines through the apoptosis mechanism. Our findings confirmed the flow cytometry results. In addition, the essential oil of Artemisia marschalliana showed a considerable cytotoxic property. Conclusion Dichloromethane extract of Artemisia marschalliana shoot and its 60 and 80% fraction selectively inhibited the growth of cancer cells by inducing the apoptosis mechanism. Regarding obtained results, 60 and 80% fractions of dichloromethane extract can be a good candidate for future studies in the field of identification and separation of pure cytotoxic compounds.